Simulation-based Assessment In Higher Education: Adapting To The Era Of Artificial Intelligence - Laura Angelini; Rut Muñiz; Roberta Diamanti (The Journal of Studies in Language, Culture and Society)
This qualitative study explores the integration of artificial intelligence (AI) in education, focusing on a simulation-based assessment methodology implemented in a Master's course in Valencia, Spain. The research addresses the growing challenges of AI in academic settings, including concerns about academic integrity, the limitations of traditional assessment methods, and the need for authentic evaluation of student competencies. By employing simulation and virtual exchange as pedagogical strategies, the study examines how pre-service teachers from nine universities engage in professional role-playing scenarios across four synchronous sessions. The research investigates the use of AI as a tool for brainstorming and organising information during these simulations. Through observations of dialogic interactions made by academic observers, the study aims to understand the potential of simulation-based learning in developing professional competencies, fostering authentic assessment, and navigating the ethical considerations surrounding AI use in education. This approach offers insights into alternative assessment methodologies that can effectively evaluate student authorship and knowledge while harnessing the advantages of AI in educational settings.